The U.S. Arctic Strategy: New Challenges - S. S. Zhiltsov (Проблемы постсоветского пространства, 2023)
The article examines the recently published documents on the priorities of the U.S. in the Arctic region. At the end of 2022, the U.S. Department of Energy published the document titled “Arctic Strategy”, and the White House released “The New National Strategy for the Arctic Region”. The latter strategic document presents the U.S. policy for the development of the Arctic over the next ten years. It addresses a number of issues, in particular rising geopolitical tension and the climate crisis, which significant effect the stable development of the Arctic re-gion. In the time of global rivalry between Russia and the West, the United States has stepped up its policy in the Arctic. The creation of these documents confirms the willingness of the United States to strengthen own presence in the region. The key directions of the U.S. policy in the Arctic, as well as areas of greatest interest to the USA are clearly defined in the strategic documents. The development of naval forces, construction of new ships, and further study of the climatic features of the Arctic region are addressed. Moreover, the documents express the U.S. firm intention to continue development of energy projects in the Arctic, and deepen cooperation with allies and partners by using multilateral mechanisms.